Makanan dan Minuman Sehat untuk Konsumsi pada Masa Covid-19: Studi Takhrij dan Syarah Hadis - Mas’ud Maulana; Hidayatul Fikra; Ai Yeni Yuliyanti; Medina Chodijah (Gunung Djati Conference Series, 2022)
The study intends to analyze hadiths about healthy foods and beverages for consumption during Covid-19. This research uses a qualitative approach that is emphasized on the study of literature through takhrij methods and hadith sharah. The results of research and discussion show that the hadith of Imam al-Bukhori No. 5011 is shahih based on takhrij review, so it can be used as a reference in charity. As for this hadith sharah shows that the Prophet really likes sweet or sweet foods made from dates mixed with milk and honey because it is beneficial for the body. This study recommends further research on the efficacy of sweets and honey, especially in treating the disease of the Covid-19 outbreak, with the collaboration of research enthusiasts of hadith science and the field of health.